Opportunity for the Implementation of Conservation Farming for Cropping Gambier in West Sumatra - . WINARDI (Jurnal Sumberdaya Lahan, 2011)
Gambier is one of the leading commodity from West Sumatra of plantation subsector. Total area gambier cultivation in West Sumatra, currently covers 18,204 ha with a production of 10,114 tons/year. Gambier planting areas are concentrated in two regions, namely District of Limapuluh Kota and District of Pesisir Selatan. Gambier is generally cultivated by traditional farmers in the forest, both protected forest and community forest. Areas with steep slopes are usually not intended as an area of cultivation. Classes of land capability in this area range from Class V to Class VIII. The low ability of farmers, whether in farming or the economic causing of gambier cultivation technology will be potluck. Such circumstances likely causing land degradation on gambier plantation. Conservation farming with agroforestry practices have an opportunity to be developped because of low cost potentially increase income and welfare. The conservation farming has been practiced by some gambier farmer